2018
DOI: 10.3390/app8040508
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things for Sensing: A Case Study in the Healthcare System

Abstract: Medical healthcare is one of the fascinating applications using Internet of Things (IoTs). The pervasive smart environment in IoTs has the potential to monitor various human activities by deploying smart devices. In our pilot study, we look at narcolepsy, a disorder in which individuals lose the ability to regulate their sleep-wake cycle. An imbalance in the brain chemical called orexin makes the sleep pattern irregular. This sleep disorder in patients suffering from narcolepsy results in them experience irrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…In a communication link, the channel properties must be known in advance, which could be analyzed with the help of wireless channel information (WCI). There exist multiple effects like scattering, fading, and multipath propagation [20], which affect the WCI of RF signal and which propagate between transmitter and receiver. The RF signal could be represented as follows,…”
Section: Design Implementation and C-band Sensingmentioning
confidence: 99%
“…In a communication link, the channel properties must be known in advance, which could be analyzed with the help of wireless channel information (WCI). There exist multiple effects like scattering, fading, and multipath propagation [20], which affect the WCI of RF signal and which propagate between transmitter and receiver. The RF signal could be represented as follows,…”
Section: Design Implementation and C-band Sensingmentioning
confidence: 99%
“…The pervasive smart environment in Internet of Things (IoTs) has the potential to monitor various human activities by using smart devices. For instance, [1] presented an approach for detecting sleep attacks due to immune system attacks, thus affecting daily activities measured using the S-band sensing method. The integration of wireless body area networks (WBANs) with recent cloud and sensor technologies offers significant improvement in the efficiency and the functionality of medical and health care systems [2].…”
Section: Introductionmentioning
confidence: 99%
“…Human activity recognition is a field often tackled by this new idea of remote sensing. Research has shown that measuring physiological signals [5,7,9,10] and general activity recognition [1,5,6,11] can all be achieved through channel state information. The user-friendliness of remote systems is higher, as no wearables are required.…”
Section: Introductionmentioning
confidence: 99%